2013
DOI: 10.4049/jimmunol.1203176
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Germinal Center B Cell Activation and T-Dependent Antibody Responses Require Expression of the Mouse Complement Receptor Cr1

Abstract: Follicular dendritic cells and complement receptors 1 and 2 are important for the generation of humoral immunity. Cr1/2 expression on B cells and FDC has been shown to provide a secondary signal for B cell activation, to facilitate transport of antigen in immune follicles, and to enhance retention of immune complexes by FDC. We show here that murine B cells predominantly express the Cr2 product from the Cr2 gene while FDC nearly exclusively express the Cr1 isoform generated from the Cr2 gene. To define the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…6). CR1/2 are expressed on both B cells and FDCs, and, according to recent data, FDCs primarily express CR1 (46). Because murine CR1 and CR2 are derived by alternative splicing from the same gene, both receptors are absent in Cr2 KO mice (51).…”
Section: Cr1/2 Expression On Both Fdcs and B Cells Is Required For Opmentioning
confidence: 97%
See 1 more Smart Citation
“…6). CR1/2 are expressed on both B cells and FDCs, and, according to recent data, FDCs primarily express CR1 (46). Because murine CR1 and CR2 are derived by alternative splicing from the same gene, both receptors are absent in Cr2 KO mice (51).…”
Section: Cr1/2 Expression On Both Fdcs and B Cells Is Required For Opmentioning
confidence: 97%
“…Determining the amount of IgG3-Ag in follicles from WT mice at various time points, we found that Ag was clearly detectable 1 h after immunization, peaked after 2 h, decreased after 4 h, and was almost undetectable after 16 h (data not shown). To determine whether Ag colocalized with FDCs, splenic sections obtained from WT mice 2 and 8 h after immunization were stained with the mAb 8C12, specific for CR1/CD35 (43) primarily expressed on FDCs (46). In mice given Ag alone, very little Ag was found in follicles after 2 h (Fig.…”
Section: Igg3-mediated Localization Of Ag To Splenic Follicles Is Depmentioning
confidence: 99%
“…In this manuscript we elaborate on our previous findings on Cr1-deficiency in mice, especially in regards to the demonstrated GC B cell deficiencies and their consequences (Donius, et al, 2013). In light of the Cr1KO ’s GC B cell deficiencies we test here the requirement for Cr1 in the production of memory B cells and high affinity antibody, while further investigating effects seen during different routes of immunization and the dependence on FDC or B cell expression of Cr1.…”
Section: Introductionmentioning
confidence: 98%
“…The inhibition of the generation of normal responses in such mice has been attributed to the deficiency of expression of Cr1/2 in the stromal compartment, most notably the FDC. FDC are responsible for the trapping of antigen via C and Fc receptors (Tew, et al, 1997, Roozendaal, et al, 2009) and for orchestrating the GC reaction (Wang, et al, 2011, Donius, et al, 2013). The recent development of a mouse specifically deficient for the Cr1 isoform of Cr2 , the Cr1KO mouse, and the revelation that Cr1 is the nearly exclusive isoform expressed by the stromal compartment FDCs, suggested that the Cr1-deficiency ( Cr1KO ) may result in a significant reduction in GC output of high affinity antibody producing cells and memory B cells (Donius, et al, 2013, Michel, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These receptors are expressed on both B cells and FDCs and may therefore function not only by localizing antigen to the FDCs but also by lowering the threshold of B cell activation via recruitment of CD19 into the BCR (Tarlinton, 1998;Donius et al, 2013). Activation of complement on FDCs is controlled by regulatory factors when these cells retain immune complexes, but some release of inflammatory mediators may cause edema that facilitates dispersion of FDC-derived "immune complex-coated bodies," or iccosomes, thereby enhancing the BCR-mediated uptake of their contained antigens Suzuki et al, 2009).…”
Section: B Cells Are Stimulated In Different Waysmentioning
confidence: 99%